2005
DOI: 10.2134/jeq2003.0238
|View full text |Cite
|
Sign up to set email alerts
|

A Regional‐Scale Study on the Crop Uptake of Cadmium from Sandy Soils

Abstract: Plant uptake is one of the major pathways by which cadmium (Cd) in soils enters the human food chain. This study was conducted to investigate the uptake of Cd by crops from soils within the wastewater irrigation area (WIA) of Braunschweig (Germany) and to develop a simple process-oriented model that is suited to predict Cd uptake at the regional scale. The sandy soils within the WIA (4300 ha) have received considerable loads of heavy metals by irrigation using municipal wastewater for up to 40 years. In 1998 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 38 publications
(45 reference statements)
1
20
0
1
Order By: Relevance
“…But the fact that the concentration of Cd in the leaves and roots fell by about half indicates that the available amount of Cd in the soil decreased with time, even though the total amount hardly changed. In a long-term wastewater disposal site (40 years) on a sandy soil in Germany, still in use, there was a linear relationship between Cd content of potato (Solanum tuberosum), sugar beet (Beta vulgaris), and winter wheat (Triticum aestivum) and the Cd concentration in the soil solution (Ingwersen and Streck, 2005; Table 1). Comparison between the studies of Granato et al (2004) and Ingwersen and Streck (2005) cannot be made, because in one study (Granato et al, 2004), total Cd in the soil was studied, and in the other (Ingwersen and Streck, 2005), Cd in solution was studied.…”
Section: Soil Factors That Control CD Bioavailabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…But the fact that the concentration of Cd in the leaves and roots fell by about half indicates that the available amount of Cd in the soil decreased with time, even though the total amount hardly changed. In a long-term wastewater disposal site (40 years) on a sandy soil in Germany, still in use, there was a linear relationship between Cd content of potato (Solanum tuberosum), sugar beet (Beta vulgaris), and winter wheat (Triticum aestivum) and the Cd concentration in the soil solution (Ingwersen and Streck, 2005; Table 1). Comparison between the studies of Granato et al (2004) and Ingwersen and Streck (2005) cannot be made, because in one study (Granato et al, 2004), total Cd in the soil was studied, and in the other (Ingwersen and Streck, 2005), Cd in solution was studied.…”
Section: Soil Factors That Control CD Bioavailabilitymentioning
confidence: 99%
“…Table 1 shows studies in which the Cd concentration has been given in both the soil and the plant. Soils have been polluted with Cd by application of sludge Granato et al, 2004;Adams et al, 2004) or wastewater (Xiong et al, 2004;Ingwersen and Streck, 2005); by being near a smelter (Brown et al, 2004;Sappin-Didier et al, 2005) or by having Cd salts added to the soil (Jiang et al, 2003;Kuo et al, 2004;Turgut et al, 2004;Evangelou et al, 2004;Dechamps et al, 2005;Li et al, 2005;Treder and Cieslinski, 2005;Patel et al, 2005;). The only study in Table 1 that reports Cd naturally in the soil is in the one by Tsadilas et al (2005), who grew tobacco with no added Cd.…”
Section: Phytoremediation By Hyperaccumulator and Nonhyperaccumulatormentioning
confidence: 99%
“…36 It has also been reported that Cd accumulation by plants grown in soil is directly related to transpiration and thereby to stomatal conductance. 19,37 Further, the ability of plants to grow on Cd contaminated soils is generally correlated with the ability of roots to exclude Cd from the plant and/or of plant tissues to chelate Cd as a non-toxic compound or sequester it in a non-vital cellular compartment. 6,38 Exposure to heavy metals results in the excessive production of ROS in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Uptake of Cd by plants depends on several plant and soil factors such as solution-phase concentration, pH, and organic carbon content. Moreover, the environmental conditions (temperature and saturation deficit) may play an important role in controlling Cd uptake (Ingwersen and Streck 2005). Anthropogenic contamination of soils by heavy metals (Cd, Pb, and Zn) occurs from many sources such as mining, atmospheric deposition from smelting operations, application of sludge, and mineral fertilizers and pesticides (Alloway 1995).…”
Section: Introductionmentioning
confidence: 99%